PS-065 Analysis of medicines errors made in a general hospital. (24th March 2015) - Lallana, E; Mañes, M; Rubio, B; Vázquez, MJ; García, JL; Segura, M
Abstract : Background: Hospital pharmacists must be focused on patient safety. Consequently, it is important to evaluate the impact of the occurrence of medicines errors (MEs). Purpose: To analyse MEs taking place in a General Hospital over a period of 5 years (2009–2013). Material and methods: Descriptive observational study of MEs reported in a General Hospital over a period of 5 years (2009–2013). Variables analysed: place, stage, drug, type, causes, consequences. Results: 422 MEs were notified in 5 years: 47, 51, 75, 111, 138. Annual growth: 8.51%, 47.06%, 48%, 24.32% respectively; overall growth: 193.62%. Place of detection: 33.65%, Hospital Pharmacy Service; 27.73%, Hospitalisation Units; 17.30%, Day Case Unit; 17.06%, Outpatient Clinics. Stage: prescription (63.74%); transcription (28.44%); dispensing, processing, supply manufacturer, validation, administration or labelling (7.82%) Drug (Anatomical Therapeutic Chemical classification): 41%, group L (Antineoplastic and immunomodulating agents); 14.22%, group J (Anti-infectives for systemic use); 11.14%, group N (Nervous system); 8.06%, group B (Blood and blood forming organs); 7.35%, group A (Alimentary tract and metabolism); 7.11%, group C (Cardiovascular system). Type: errors in dosage (36.02%), inappropriate medicine (24.64%) or patient (22.27%). Causes: lack of staff training (29.86%), lack of compliance of work procedures (27.25%), incorrect patient identified (14.93%), insufficient staff, without experience or under stress conditions (13.51%), problems in interpreting the prescription (11.85%). Consequences: the error did not reach the patient (70.14%); the error came to the patient but did not cause any damage (16.35%); circumstances or events which may cause error (10.19%). Conclusion: Reporting of MEs is increasing significantly, although the corresponding data are undervalued. Therefore, it is important to continue working on this aspect. It is crucial to report and analyse in detail the MEs taking place in hospitals. This way, the real conditions in which they occur can be known, and improvement strategies can be adopted to improve the safety. References and/or acknowledgements: No conflict of interest.